How does the Increase in Electricity Price Change Behavior of Households in Craft Production? A Case Study in Craft Villages, BAC Ninh Province Vietnam - Ninh, Nguyen Thi Hai; Lebailly, Philippe; Dung, Nguyen Mau (International Journal of Economics and Financial Issues, 2018)
The findings of the research on 120 production households in craft villages show that steel producers are more affected by electricity price increase rather than woodcarving one. This is because steel households use more high power machines which make electricity cost is approximate 25 times higher than that cost of woodcarving housholds and is accounted for 5% of total production cost. When electricity price increasing, craft households choose three main solutions to adapt including: invest in new machines using less electricity power; change to produce in mid-night when electricity price is low; and move to make products which spend less electricity power. Base on ARIMA (3,1,1) and ARIMA (1,1,4) models, the forecast for electricity demand of craft households in short term identify that if electricity price increases 7.5%, profit of steel households will decrease over 3 millions dong per month whereas profit of wood households is not significantly dropped. Keywords: Electricity Price, Craft Production Household, ARIMA model JEL Classifications: O1, O2, C5